Oficinas de Memória como recurso protetivo no processo de envelhecimento normal e sua repercussão na autoestima e qualidade de vida. São Bernardo do Campo 2019 - Schultheisz, Thais Sisti De Vincenzo (2019)
In Brazil, data from the last census of 2015 indicate that 14.3% of a total of 204,450,649 habitants correspond to the population aged 65 or over. Expectations from the World Health Organization indicate that, in 2025, Brazil will be the sixth country in the world with the largest number of elderly. Despite the many advances, the changes resulting from aging are a universal phenomenon. However, it should be noted that aging tends to be still regarded as an illness or the end of life. The objective of this study was to verify the contribution of memory workshops as a protective resource for cognitive impairments in self - esteem and quality of life in the elderly. It is an interventional, transversal and prospective research. Participants in this study were 44 elderly people of both sexes with and without complaints of memory, members of “Projeto Aquarela” from University Metodista de São Paulo (UMESP) – Campus Rudge Ramos . The research consists of three stages: The first included the demographic data collection, and cognitive measures, of self-esteem and quality of life. The second with development of 12 sessions of memory workshops. The third with reassessment of cognitive aspects, self-esteem and quality of life. The instruments used were: Sociodemographic questionnaire. For Cognitive Assessment: (WAIS-III subtest), Logical Memory, Trail Making Test A and B, Rey Complex Figure, Verbal Fluency - (FAS). For quality of life the WHOQOL-Bref and self-esteem Rosenberg Scale. All participants signed the